Tingkat Pengetahuan, Dukungan Keluarga dan Persepsi Masyarakat Tentang Vaksinasi Dosis Penguatan Terhadap Varian COVID-19 - Dharmapatni , Ni Wayan Kesari; Swarjana, I Ketut; Harditya, Kadek Buja (Jurnal Kesehatan, 2023)
The World Health Organization (WHO) has made various efforts to reduce the number of COVID-19 victims globally. Many researchers are trying to develop a vaccine from this virus, but the vaccines that have been made are still considered not fully able to stop this pandemic. The efforts of the Government of the Republic of Indonesia have been made to accelerate the recovery of pandemic conditions into an endemic, by distributing the COVID-19 vaccine as the implementation of booster vaccinations. However, with the circulation of various negative news related to the COVID-19 vaccine and the development of viruses that continue to mutate, these affects the acceptance and willingness of the community in the implementation of covid-19 vaccination. The purpose of this study was to determine the level of knowledge, family support and community perceptions about booster dose vaccination against COVID-19 variants. The research design used was quantitative research with descriptive method. The sampling method used was snowball sampling, with a total of 317 respondents. After analyzing the data, the results showed that the community had a good level of knowledge (78.5%), a good level of family support (94%) in vaccinating and had a positive perception (99.7%) of the booster dose vaccination COVID-19. This study is expected to provide an overview for health workers to achieve success and follow-up strategies to restore conditions towards a better condition.